Direct electrochemical reduction of carbon dioxide by a molybdenum-containing formate dehydrogenase - Cordas, Cristina M. (2022)
This work was supported by the Associate Laboratory for Green Chemistry -LAQV, with national funds from FCT/MCTES ( UID/QUI/50006/2019 ). LBM thanks to FCT/MCTES for the CEEC-Individual 2017 Program Contract.